Analýza pohlavních chromosomů kropenatce jetelového (Chiasmia clathrata) (Lepidoptera, Geometridae) - Trehubenko, Marharyta (Jihočeská univerzita, 2020)
The aim of this thesis was to identify the cause of the variability of the sex chromatin in Chiasmia clathrata (Geometridae). I tested several hypotheses, namely variability in the W chromosome appearance, absence of the W chromosome in some females (i.e. Z0 females), feminization by intracellular symbiont Wolbachia (i.e. ZZ females), and presence of extranumerary B-chromosomes. My results excluded Wolbachia as a potential cause of variability. I found B-chromosomes across families with (SC+) and without sex chromatin (SC-), which suggests they are not responsible for sex chromatin variability. In some nuclei of SC- females, univalents occur, possibly representing either single Z or B chromosome. Finally, comparative genomic hybridization failed to detect a W chromosome, but genomic in situ hybridization highlighted the W chromosome in one family with sex chromatin (SC+), suggesting the existence of a neo-W system.
Analysis of latticed heath (Chiasmia clathrata) sex chromosomes